Elections, Democracy and Disabled People - Traustadóttir, Rannveig; Rice, James G. (Stjórnsýslustofnun, 2017)
The right to vote is a fundamental right of citizenship in democratic nations, and participation in elections in one of the most important acts undertaken by citizens. Although these rights are guaranteed to all citizens, international research shows that disabled people are widely excluded from participation in elections. Disabled people are less likely to vote than non-disabled people and often encounter various obstacles when they try to participate in elections. This article discusses the voting participation of disabled people in consideration of the international research. The main barriers that disabled people encounter in the voting process will first be outlined. This will be followed by questions concerning the effects these obstacles produce, not only for disabled citizens, but what this means overall for the health of democracy and democratic institutions when a portion of the citizenry encounter serious obstacles concerning their basic civil rights. Icelandic research in this field is extremely limited and no systematic statistical data exists on the participation of disabled people in elections, or politics in general, in this country. Based on data drawn from sources from two of the largest disabled people’s organization in the country, the focus here is on the experiences, circumstances and opportunities for disabled people to participate in elections in the country. The findings draw attention to the obligations of the state to promote and ensure the participation of disabled people in politics and public life in light of the recent ratification in Iceland of the UN Convention on the Rights of Persons with Disabilities (CRPD). Kosningaréttur er grundvallarréttur þegna í lýðræðisríkjum og þátttaka í kosningum álitin ein af mikilvægustu athöfnum borgaranna. Þó að þessi réttindi skuli tryggð öllum þegnum sýna alþjóðlegar rannsóknir að fatlað fólk er víða útilokað frá þátttöku í kosningum. Fatlað fólk er síður líklegt til að kjósa en ófatlað fólk og mætir iðulega ýmsum hindrunum ef það reynir að ...